In vivo pathogenic properties of two clonal human immunodeficiency virus type 1 isolates. - Jamieson, B D (1995)
We have investigated the in vivo pathogenic properties of two molecularly cloned strains of human immunodeficiency virus type 1 (HIV-1), HIV-1NL4-3 and HIV-1JR-CSF, in human fetal thymus/liver implants in severe combined immunodeficient mice. Studies comparing their in vivo replication kinetics and abilities to induce CD4+ thymocyte depletion were performed. HIV-1NL4-3 replicated in vivo with faster kinetics and induced greater levels of CD4+ thymocyte depletion than did HIV-1JR-CSF. These results demonstrate that different viral isolates have different pathogenic properties in this system. In the SCID-hu model, this pathogenesis most likely occurs in the absence of an immune response. Therefore, we investigated whether the absence of immune selection resulted in extensive genetic variation and the generation of viral quasispecies. To this end, DNA corresponding to the fourth variable domain region of the viral envelope gp120 protein recovered from biopsy samples at 6 weeks postinfection was sequenced. Little genetic variation was noted in either HIV-1JR-CSF- or HIV-1NL4-3-infected implants. The mutation levels demonstrated in both viral strains were more reflective of the acute rather than the chronic phase of HIV-1 infection in humans. These results suggest that the SCID-hu mouse model can be used to study the in vivo pathogenicity of different HIV-1 isolates in the absence of host immune selective pressures.